Analisis dan Strategi Peningkatan Pendapatan Asli Daerah (PAD) di Kabupaten Gunungkidul - Evi Nilawati (Universitas Proklamasi 45 Yogyakarta, 2019)
Regional Original Revenue (PAD) has a very large contribution to the Regio-nal Budgeting (APBD) to finance the administration and service processes of govern-ment affairs and regional development. The present research aims to determine how to improve PAD and build strategy of action plan for increasing it in Gunungkidul Regency. This study used descriptive qualitative method. Informants were taken by purposive sampling. Data collecting techniques are observations, interview with Local Agency Organizations (OPD) which are responsible for PAD generation, and docu-mentations or secondary data, i.e. APBD, PAD, and other relevant data. The results of the study showed that the development of Gunungkidul PAD experienced a significant development as big as 25,97%. The PAD contribution to regional income or fiscal decentralization rate is 11,73%. The strategy to increase the PAD is built by a formulating action plan for accelerating it. Based on this results, it is suggested that the program to increase competency and commitment of regional tax-retribution managers for each revenue management of local agency, provide a program to increase the PAD and implementation of the action plan to increase it, use information and communi-cation technology for the management of each PAD lines, and optimally stakeholders cooperation building.